ASPEK MANAJEMEN DALAM TATALAKSANA PNEUMONIA PADA BALITA DI PROVINSI RIAU TAHUN 2020-2022 - Septemdelti, Mona; Jepisah, Doni; Anusirwan, Anusirwan (Ensiklopedia of Journal, 2024)
Reports of pneumonia cases in toddlers in Riau Province in the last 3 years (2020-2022), namely in 2022 pneumonia cases in toddlers amounted to 2179 cases, in 2021 89 cases and in 2022 amounted to 1934 cases. The purpose of the study was to determine the implementation of pneumonia management in children under five in Riau Province in 2020-2022. The research method was conducted descriptively by identifying problems according to man, money, method, machine, material, and environment. Then determine alternative problem solving using Fish Bone Analysis and create an intervention plan matrix. The results of the study showed that the implementation of the management of under-five pneumonia cases in Riau Province still has several obstacles such as the officers involved are not competent, have a double workload and have not participated in technical guidance, limited budget, limited drug logistics and some areas that are difficult to reach. It is recommended to recruit human resources according to competence, improve cross-sectoral cooperation, propose the need for additional procurement of pneumonia drug logistics in children under five.Keywords: Toddlers, Pneumonia, Human Resource.